BIOSORPSI ION LOGAM Cd2+ MENGGUNAKAN BATANG KECOMBRANG (Etlingeraelatior) SEBAGAISUMBER BELAJAR BERBASIS POWER POINT - warsono adinata; lazulva lazulva (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
This research aimed at seeing the appropriateness of the instructional media Power Point based. The early stage conducted was seeing the basic competence that needed the instructional media adapted to the syllabus of Vocational High School of Pharmacy Pekanbaru. The material was Adsorption material that was on the basic competence of 1.2, it was about understanding the adsorption process. After adjusting the material, applied research of biosorption of Cd2+ metal ion using Kecombrangtrunk on various pH 2, 3, 4, 5, and 6 that was analyzed by AAS was conducted. The optimum pH obtained was on pH 5 with 80.73% adsorption. The next step was preparing the instructional media Power Point based that was assessed by material and media experts. The result of material expert assessment showed their strong agreements and there was no revision with 82% percentage. The next step was testing 4 Chemistry teachers at Vocational High School of Pharmacy Pekanbaru. It showed the agreement and no revision with 79.75% percentage. It meant that the chemistry instructional media Power Point based could be a learning resource.Keywords: Learning Resources, Instructional Media Power Point Based, Kecombrang,Cadmium, Adsorption.